Intervention of Musculoskeletal Discomfort Risk: A Cross-Sectional Study - Hutabarat, Julianus; Alfian Pradana, Johan; Achmadi, Fuad; Wilis Lestarining Basuki, Diah (KnE Social Sciences, 2024)
Driving activity for online motorcycle taxi drivers is dominantly causing static activity. This static activity plays a role in creating complaints of musculoskeletal disorders. This study aimed to determine the point on the body that is affected by static activity and the value of the Nordic Body Maps (NBM) of the characteristics of the respondents. The methodology used is a chi-square test with 70 respondents as the sample. The research stage began with distributing NBM questionnaires and then assessed descriptively. Furthermore, the chi-square test played a role in assessing the significant relationship. It was found that the dominant complaint point was the back. The influential correlations include the left shoulder on Body Mass Index (BMI) correlation, waist to height and age, hips to height, left elbow to height, and right knee to BMI. It is hoped that an intervention is needed to minimize musculoskeletal disorders with post-driving stretching activities. Keywords: static activity, musculoskeletal disorders, Nordic Body Map